Resting-State Phase-Amplitude Coupling Between the Human Subthalamic Nucleus and Cortical Activity: A Simultaneous Intracranial and Scalp EEG Study - Damborská, Alena; Lamoš, Martin; Brunet, Denis; Vulliemoz, Serge; Bočková, Martina; Deutschová, Barbora; Baláž, Marek; Rektor, Ivan (Brain topography, 2021)
It has been suggested that slow oscillations in the subthalamic nucleus (STN) reflect top-down inputs from the medial prefrontal cortex, thus implementing behavior control. It is unclear, however, whether the STN oscillations are related to cortical activity in a bottom-up manner. To assess resting-state subcortico-cortical interactions, we recorded simultaneous scalp electroencephalographic activity and local field potentials in the STN (LFP-STN) in 11 patients with Parkinson's disease implanted with deep brain stimulation electrodes in the on-medication state during rest. We assessed the cross-structural phase-amplitude coupling (PAC) between the STN and cortical activity within a wide frequency range of 1 to 100 Hz. The PAC was dominant between the δ/θ STN phase and β/γ cortical amplitude in most investigated scalp regions and between the δ cortical phase and θ/α STN amplitude in the frontal and temporal regions. The cross-frequency linkage between the slow oscillations of the LFP-STN activity and the amplitude of the scalp-recorded cortical activity at rest was demonstrated, and similar involvement of the left and right STNs in the coupling was observed. Our results suggest that the STN plays a role in both bottom-up and top-down processes within the subcortico-cortical circuitries of the human brain during the resting state. A relative left-right symmetry in the STN-cortex functional linkage was suggested. Practical treatment studies would be necessary to assess whether unilateral stimulation of the STN might be sufficient for treatment of Parkinson's disease.
Keywords: Scalp; Subthalamic Nucleus; Electroencephalography; Humans; lidé; Parkinson Disease; elektroencefalografie; nucleus subthalamicus; Deep Brain Stimulation; hluboká mozková stimulace; skalp; Parkinsonova nemoc